MiR-361-5p promotes proliferation and inhibits apoptosis of fibroblast-like synoviocytes via targeting ZBTB10 in rheumatoid arthritis - Aixian Zhang; Rong Lu; Huifang Lang; Min Wu (Taylor & Francis Group, 2022)
Objectives This study is aimed to explore the key role of miR-361-5p in fibroblast-like synovial (FLS) cells of rheumatoid arthritis (RA) and explore the underlying mechanism. Methods First, we performed RT-qPCR to evaluate the expression of miR-361-5p in both synovial tissues of RA patients and cultured RA-FLS cells. Then CCK-8 assay, EdU staining, Western blot, flow cytometry, and ELISA were conducted to estimate the influence of inhibiting miR-361-5p on RA-FLS cells. Moreover, we used bioinformatics analysis to predict the potential targets of miR-361-5p and perform a dual luciferase report assay for verification. Finally, rescue experiments were performed to prove the role of miR-361-5p/Zinc Finger And BTB Domain Containing 10 (ZBTB10) in the proliferation, cell cycle, and apoptosis of RA-FLS. Results We find that the expression of miR-361-5p is increased in both RA tissues and cultured RA-FLS cells. The inhibition of miR-361-5p can not only inhibit proliferation, arrest the cell cycle in G1/G0 phase, and increase apoptosis, but also reduce the inflammatory factors secreted by RA-FLS cells. In addition, ZBTB10 is a direct target for miR-361-5p, over-expression of ZBTB10 reverses the effect of miR-361-5p in RA-FLS. Conclusions MiR-361-5p promotes the progression of rheumatoid arthritis by targeting ZBTB10.Key points The influences of miR-361-5p on RA-FLS cells.